Student Perspectives About Goal Orientation, Quality of Educator Accountants, Practitioners and Non Practitioners on the Quality of Accounting Students: Perspektif Mahasiswa Tentang Goal Orientation, Kualitas Akuntan Pendidik, Praktisi dan Non Praktisi Terhadap Kualitas Mahasiswa Akuntansi - Mulyadi, Akhmad; Sari, Dewi Komala; Noor Abidin, Fityan Izza (Universitas Muhammadiyah Sidoarjo, 2022)
In this study, the objectives to be achieved are: Testing the effect of Goal Orientation on the Quality of Accounting Students.Testing the influence of the Quality of Accountants Educating Practitioners on the Quality of Accounting Students. Testing the effect of the Quality of Accountants Educating Non-Practitioning on the Quality of Accounting Students. The sample used in this study was 126 respondents from accounting students at the Muhammadiyah University of Sidoarjo in semesters 6 and 8. The primary data used was obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The analytical tool used is multiple linear regression analysis, t test and F test using SPSS (Statistical Package for Social Science) version 18.0 for windows. The results of the research based on the validity and reliability test showed that the data obtained were valid and reliable. Based on the t-test shows the results that Goal Orientation has no significant effect on the Quality of Accounting Students. While the Quality of Practitioner Educator Accountants has a significant influence on the Quality of Accounting Students. However, the Non-Practical Educator Accountant Quality variable shows that the Non-Practical Educator Accountant Quality does not have a significant effect on the Accounting Student Quality.